Survey of Student Satisfaction Level in the PJOK Learning Implementation Process Using the Merdeka Curriculum at Bina Agung Private Junior High School - Ibrahim, Ibrahim; Ginting, Dodi Ferdinanta; Fauza, Muhammad; Oktariska, Salsa; Saragih, Juan Prima; Hutagalung, Rinaldi Rahman; Sihite, Kristini; Rahma, Fanisa; Tamimi, Fa'id Aqdas; Mendrofa, Iradat Lidwina; Sagala, Ronaldo; Silaban, Daniel (Journal Coaching Education Sports, 2025)
The purpose of this study was to determine the level of student satisfaction in the process of implementing PJOK learning using the Merdeka Curriculum at Bina Agung Private Junior High School. The method used in this research is the survey method. The population used was all students at Bina Agung Private Junior High School and the research sample used was 68 students at Bina Agung Private Junior High School. The instrument used in this research is a questionnaire, while the variable in this study is the level of student satisfaction in the process of implementing PJOK learning using the Merdeka Curriculum at Bina Agung Private Junior High School and the data analysis technique used is descriptive qualitative and quantitative. The results showed that the level of student satisfaction in the process of implementing PJOK learning using the Merdeka Curriculum at Bina Agung Private Junior High School which has been carried out by 68 students who were selected as samples in the study at Bina Agung Private Junior High School has a percentage of 86% very satisfied category, consisting of 3 school levels consisting of VII class 28 students have a value of 2612 with a percentage of 87% very satisfied category, VIII class 21 students have a value of 2243 with a percentage of 85% very satisfied category and IX class 23 students have a value of 2427 with a percentage of 84% very satisfied category.